Little Impact of NaCl Reduction in Swiss-Type Cheese - Gagnaire, Valérie; Lecomte, Xavier; Richoux, Romain; Genay, Magali; Jardin, Julien; Briard-Bion, Valérie; Kerjean, Jean-René; Thierry, Anne (Frontiers in Nutrition, 2022)
Reducing salt intake can mitigate the prevalence of metabolic disorders. In fermented foods such as cheeses, however, salt can impact the activity of desirable and undesirable microorganisms and thus affect their properties. This study aimed to investigate the effect of salt level on Swiss-type cheese ripening. Since proteolysis is a major event in cheese ripening, three strains of Lactobacillus helveticus were selected on the cell-envelope proteinase (CEP) they harbour. Their proteolytic activity on caseins was studied at six salt levels (0 to 4.5%) at pH 7.5 and 5.2. Swiss-type cheeses were manufactured at regular, increased, and decreased salt concentrations, and characterised for their composition and techno-functional properties. L. helveticus strains possessed and expressed the expected CEPs, as shown by PCR and shaving experiments. The two strains of L. helveticus that possessed at least the CEP PrtH3 showed the greatest proteolytic activity. Casein hydrolysis in vitro was similar or higher at pH 5.2, i.e. cheese pH, compared to pH 7.5, and slightly decreased at the highest salt concentrations (3.0 and 4.4%). Similarly, in ripened cheeses, these L. helveticus strains showed 1.5 to 2.4 more proteolysis, compared to the cheeses manufactured without L. helveticus. Regarding the salt effect, the 30% salt-reduced cheeses showed the same proteolysis as regular cheeses, while the upper-salted cheeses showed a slight decrease (-14%) of the non-protein fraction. The microbial and biochemical composition remained unchanged in the 30%-reduced cheeses. In contrast, Propionibacterium freudenreichii, used as ripening bacteria in Swiss cheese, grew more slowly in upper-salted (1.14%, w/w) cheeses, which induced concomitant changes in the metabolites they consumed (- 40% lactic acid) or produced (5-fold decrease in propionic acid). Some cheese techno-functional properties were slightly decreased by salt reduction, as extrusion (-17%) and oiling off (-4%) compared to regular cheeses. Overall, this study showed that a 30% salt reduction has little impact in the properties of Swiss-type cheeses, and that starters and ripening cultures strains could be chosen to compensate changes induced by salt modifications in Swiss-type and other hard cheeses.